PENGARUH PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAME TOURNAMENT (TGT) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTSN LIMBANANG KAB. LIMA PULUH KOTA - Sari, Vera Yolanda; Rahmi, Rahmi; Zulfaneti, Zulfaneti (STKIP PGRI Sumbar, 2013)
This research is motivated by the studentsâ poor understanding of mathematical concepts, so that they frequently did not complete the tasks submitted by the teacher. The research aims to determine whether implementing cooperative learning model Team Games Tournament (TGT) is better than the conventional learning to improve studentâs understanding of mathematical concepts for VIII-grade students of MTsN Limbanang, 50 Kota. This research is experimental, using random sampling of population.Â The population studied is five classes of VIII-grade students of MTsN Limbanang, 50 Kota. Samples taken ramdomly from the selected classes: VIII.1 class as the experimental class and VIII.2 class as the control class. The instrument used in this study is a test of studentsâ understanding of mathematical concepts. The test form is essay with reliability r11=0.869. From the data analysis obtained the mean of the experimental class is 76.6 and 61.9 for the control class. The one side test of hypothesis (t-test) using MINITAB shows Pvalue 0.002 which less than Î± 0.05; so that the hypothesis proposed on the trust level 95% is accepted. It can be concluded that the students understanding of mathematical concepts by implementing cooperative learning Team Games Tournament ( TGT ) is better than conventional learning.